A Windswept Archipelago: Stories of Perception, Time and Landscape in the Orkney Islands - Friend, Sara Bowman (The Unfamiliar, 2015)
This paper explores the interconnection between individual experience, place and time in the Orkney Islands of Scotland, an island now renowned for the generation and development of renewable energy. I consider and discuss three informant's comments on wind turbines in particular. Each ethnographic example I include expresses its own time-orientation. The aim is to draw out the complexities of the difference in perception and opinion experienced by each example, in order to discuss why and how difference in perception and experience of the landscape occurs and why it matters.